2021
DOI: 10.1021/acs.jmedchem.1c01067
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Reldesemtiv, a Fast Skeletal Muscle Troponin Activator for the Treatment of Impaired Muscle Function

Abstract: The discovery of reldesemtiv, a second-generation fast skeletal muscle troponin activator (FSTA) that increases force production at submaximal stimulation frequencies, is reported. Property-based optimization of high throughput screening hit 1 led to compounds with improved free exposure and in vivo muscle activation potency compared to the first-generation FSTA, tirasemtiv. Reldesemtiv demonstrated increased muscle force generation in a phase 1 clinical trial and is currently being evaluated in clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…This difluoromethyl analogue was smoothly furnished in 60% yield. Lastly, 2w , prepared in 69% yield from Tirasemtiv, contains an imidazo­[4,5- b ]­pyrazinone scaffold commonly encountered in small molecules that target muscle weakness caused by neurogenic diseases. , Throughout the exploration of the substrate scope, we encountered two limitations of the method. Compounds with scaffolds like F1 or F2 were not able to undergo difluoromethylation under these conditions (Scheme i) and instead, 1,1,2,2-tetrafluoroethane { 19 F NMR (CDCl 3 ) δ −139 (d, 55 Hz)} was formed as the major product (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…This difluoromethyl analogue was smoothly furnished in 60% yield. Lastly, 2w , prepared in 69% yield from Tirasemtiv, contains an imidazo­[4,5- b ]­pyrazinone scaffold commonly encountered in small molecules that target muscle weakness caused by neurogenic diseases. , Throughout the exploration of the substrate scope, we encountered two limitations of the method. Compounds with scaffolds like F1 or F2 were not able to undergo difluoromethylation under these conditions (Scheme i) and instead, 1,1,2,2-tetrafluoroethane { 19 F NMR (CDCl 3 ) δ −139 (d, 55 Hz)} was formed as the major product (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…It selectively binds the troponin complex, slows the release of calcium from troponin C, and sensitizes the sarcomere to calcium. This makes the force-calcium relationship of muscle fibers and force-frequency relationship of a nerve-muscle pair shift leftwards, increasing the muscle’s response to neural input and enhancing strength at submaximal stimulation frequencies ( Collibee et al, 2021 ; Shefner et al, 2021 ). The restoration of skeletal muscle function may preserve the integrity of NMJs and slowing the impairment of motor neurons ( Lepore et al, 2019 ).…”
Section: Drugsmentioning
confidence: 99%
“…Reldesemtiv is more potent than the first-generation fast skeletal muscle troponin activator tirasemtiv, which shares the same mechanism ( Li et al, 2021 ), as it does not cross the blood‒brain barrier, is associated with milder adverse events, and the doses are lower ( Collibee et al, 2021 ). The results from a phase 2 study showed that Reldesemtiv was well tolerated.…”
Section: Drugsmentioning
confidence: 99%
“…Cardiac sarcomere activators continue to be explored as potential new treatments in heart failure with reduced ejection fraction (HFrEF). 1,2 An area of continued unmet medical need for heart failure patients is in conditions where the contractility of the right ventricle is reduced. For example, congenital heart disease (CHD) is characterized by a range of cardiac birth defects that affect the normal function of the heart.…”
Section: ■ Introductionmentioning
confidence: 99%